INFORMEDNESS OF COLLEGE STUDENTS AS BANK CUSTOMERS - Surya, Gande (International Journal of Research -GRANTHAALAYAH, 2020)
Banks are the institutions where most of the people put their hard-earned money in. But do they really know about banks - their services, their terms and conditions, their tariff plans, their communications and the dispute resolution mechanisms? This study tried to find out this by, interviewing 100 young college-going bank customers. The surprising results of this study led to some suggestions which require immediate implementation.